2020
DOI: 10.14283/jfa.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on COVID-19 Negative Geriatric Patients with Hip Fractures

Abstract: Since December 2019, the novel coronavirus (COVID-19) had affected millions globally, particularly putting elderly and persons with chronic diseases at risk (1). 95% of all COVID-19 deaths in Singapore are older adults (2). As public health policymakers try to control the pandemic by focusing resources on COVID-19, the general population fear contracting coronavirus from hospitals, resulting in changes in their healthcare seeking behaviour. We describe two cases demonstrating the direct and indirect impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…[13][14][15] In some reports, the hip fracture management changes during the COVID-19 pandemic impacted mortality and morbidity even in COVID-19-negative patients. [16] However, the evidence is conflicting, and research analyzing the COVID-19 pandemic impact on hip fracture patient care in the US is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] In some reports, the hip fracture management changes during the COVID-19 pandemic impacted mortality and morbidity even in COVID-19-negative patients. [16] However, the evidence is conflicting, and research analyzing the COVID-19 pandemic impact on hip fracture patient care in the US is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Operating room capacity and staffing decreased significantly in many hospitals in response to COVID-19 patient care needs and staff infections [13–15] . In some reports, the hip fracture management changes during the COVID-19 pandemic impacted mortality and morbidity even in COVID-19-negative patients [16] . However, the evidence is conflicting, and research analyzing the COVID-19 pandemic impact on hip fracture patient care in the US is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…As public health policymakers tried to control the pandemic by focusing resources on COVID-19, the general population was afraid of contracting coronavirus from hospitals, resulting in changes in their healthcare seeking behaviour. 2 This was more pronounced in the geriatric age group patients as well as in their attendants. The adjustment of hospital policies also contributed to the need for innovation in the management of these fractures.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, COVID-19 impacted key healthcare standards for high-quality hip fractures care, specifically time to surgery, which reflects the difficulty of maintaining normal workflow during the pandemic due to a significant decrease in the availability of operating rooms and healthcare staff. Several studies have also reported an increase in the rate of severe complications and mortality rate during the pandemic, even in COVID-19-negative patients 14 .…”
Section: Introductionmentioning
confidence: 97%